Skills and earnings : a multidimensional perspective on human capital - Wössmann, Ludger [Verfasser] (My University, 2024)
„The multitude of tasks performed in the labor market requires skills in many dimensions. Traditionally, human capital has been proxied primarily by educational attainment. However, an expanding body of literature highlights the importance of various skill dimensions for success in the labor market. This paper examines the returns to cognitive, personality, and social skills as three important dimensions of basic skills. Recent advances in text analysis of online job postings and professional networking platforms offer novel methods for assessing a wider range of applied skill dimensions and their labor market relevance. A synthesis and integration of the evidence on the relationship between multidimensional skills and earnings, including the matching of skill supply and demand, will enhance our understanding of the role of human capital in the labor market.“ (author‘s abstract; BIBB-Doku)

„Traditionellerweise wird Humankapital vor allem durch Bildungsabschlüsse dargestellt. Die Literatur weist jedoch zunehmend auf die Bedeutung verschiedener Kompetenzdimensionen für den Erfolg am Arbeitsmarkt hin. Das vorliegende CESifo Working Paper fasst die Evidenz zu Erträgen kognitiver, persönlicher und sozialer Kompetenzen als drei wichtige Dimensionen von Basiskompetenzen zusammen. Jüngste Fortschritte bei der Textanalyse von Online-Stellenausschreibungen und professionellen Plattformen bieten neue Methoden zur Messung einer breiteren Palette angewandter Kompetenzdimensionen und ihrer Arbeitsmarktrelevanz.“ (Hrsg.; BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; S 4.3.6 Human Capital; 370; 330; Humankapital; Schlüsselqualifikation; Kognitive Fähigkeit; Selbstkompetenz; Kompetenzforschung; Sozialkompetenz; Qualifikationsverwertung; Einkommenseffekte